2021
DOI: 10.1186/s12884-021-04054-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, risk factors and management of post cesarean section surgical site infection (SSI) in a tertiary hospital in Egypt: a five year retrospective study

Abstract: Background Surgical site infection (SSI) is one of the commonest complications following cesarean section (CS) with a reported incidence of 3–20%. SSI causes massive burdens on both the mother and the health care system. Moreover, it is associated with high maternal morbidity and mortality rate of up to 3%. This study aims to determine the incidence, risk factors and management of SSI following CS in a tertiary hospital. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
36
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 38 publications
5
36
4
1
Order By: Relevance
“…This study found a 6.0% prevalence of SSIs. This was in line with earlier findings from Egypt (5.3%) [33], Ankara (6.2%) [34], Pennsylvania (6.5%) [34], and SSA (7.3%) [35]. Conversely, the prevalence of SSIs found in our study was lower than what was found in similar studies with a prevalence of 10.9% in Tanzania [36], 11% in Ethiopia [37], 16.2% in Nigeria [38], 12.6% in Nepal [39] and 24.3% in Pakistan [40].…”
Section: Discussionsupporting
confidence: 94%
“…This study found a 6.0% prevalence of SSIs. This was in line with earlier findings from Egypt (5.3%) [33], Ankara (6.2%) [34], Pennsylvania (6.5%) [34], and SSA (7.3%) [35]. Conversely, the prevalence of SSIs found in our study was lower than what was found in similar studies with a prevalence of 10.9% in Tanzania [36], 11% in Ethiopia [37], 16.2% in Nigeria [38], 12.6% in Nepal [39] and 24.3% in Pakistan [40].…”
Section: Discussionsupporting
confidence: 94%
“…There are few studies describing the incidence of PPCs after CD. Cardiovascular events are reported to occur in 0.2% of CD patients [8], infectious complications are reported to occur in 5-9% of patients [9][10][11], and VTEs are reported to occur in 0.3% of patients [12]. To our knowledge and based on our literature review, few studies have explored racial disparities in PPCs after CD.…”
Section: Discussionmentioning
confidence: 93%
“…These complications contribute not only to mortality, but also to morbidity in patients [8]. Surgical site infections (SSIs) are defined as infections occurring within 30 days post-operation and affecting superficial or deep incisional sites, or deeper-lying spaces or organs [9,10]. SSIs are also associated with increased healthcare costs, longer hospitalization, and more patient dissatisfaction [11].…”
Section: Introductionmentioning
confidence: 99%